Association of changes in histologic severity of nonalcoholic steatohepatitis and changes in patient‐reported quality of life. Issue 10 (28th July 2022) - Heath, Laura; Aveyard, Paul; Tomlinson, Jeremy W.; Cobbold, Jeremy F.; Koutoukidis, Dimitrios A.
Abstract: Nonalcoholic steatohepatitis (NASH) is a prevalent chronic disease that is associated with a spectrum of liver fibrosis and can lead to cirrhosis. Patients with NASH report lower health‐related quality of life (HRQoL) than the general population. It remains uncertain how changes in histologic severity are associated with changes in HRQoL. This is a secondary analysis of the Farnesoid X Receptor Ligand Obeticholic Acid in NASH Treatment (FLINT) and Pioglitazone, Vitamin E, or Placebo for Nonalcoholic Steatohepatitis (PIVENS) randomized controlled trials in patients with biopsy‐proven NASH. HRQoL was assessed using short form‐36 at baseline and at follow‐up biopsy (at 72 and 96 weeks, respectively). Adjusted linear regression models were used to examine the association between changes in liver fibrosis (primary analysis), nonalcoholic fatty liver disease (NAFLD) activity score (secondary analysis), and changes in HRQoL scores. Compared with stable fibrosis, improvement of fibrosis by at least one stage was significantly associated with improvements only in the physical function component by 1.8 points (95% confidence interval, 0.1, 3.5). Worsening of fibrosis by at least one stage was not associated with statistically significant changes in any HRQoL domain compared with stable fibrosis. Associations between HRQoL and NAFLD disease activity score in the secondary analysis were of similar magnitude. Weight loss was associated with small improvements in physical function, general health, and energy levels. Conclusion : Improvements in fibrosis stage were associated with improvements in the physical component of HRQoL, but the clinical impact was modest. As improving fibrosis may not meaningfully improve well‐being, treatment for NASH will be cost effective only if it prevents long‐term hepatic and cardiovascular disease. Abstract : People with serious liver disease due to excess body weight typically have lower quality of life than the general population. In this study, we explored whether changes in disease severity is associated with changes in patient reported quality of life from secondary analysis of two randomised controlled trials. We found that some improvements in liver disease were associated with small improvements in patient reported health reported quality of life.image